Effect of maturity on the mineral content of hairy vetch (Vicia villosa) - T. P. Lanyasunya (Tropical and Subtropical Agroecosystems, 2007)
This study was conducted in Naivasha, Kenya over aperiod of 15 weeks to determine the effect of maturityon mineral content in hairy vetch (Vicia villosa Roth).Immediately after field preparation, 60 plots 2 x 2 sq.m size were demarcated and allotted to 5 similarblocks of 12 plots each in a randomized completeblock design. Each plot received 10 g of seed evenlydrilled to 5 rows (2 m length and 30 cm apart). All theplots were planted on the same day and kept weed freethroughout the study. They were harvested at 6, 8, 10,12 and 14 weeks after seed emergence in sequentialmanner beginning with block 1 to 5, each time leavinga stubble height of 5 cm. Levels of most elementsexamined were not strongly influenced by advancingmaturity of V. villosa. P, Na and Mg levels remainedfairly constant with advancing maturity of the legume.Their overall means at the end of the study were 36.8,160.4 and 17 g kg-1 DM respectively. Concentrationlevels of Mn and Zn also followed the same patternover the study period. Levels of K however increasedsharply from 29.4 at 6 to 42.1 g kg-1 DM at 14 weeks.Copper levels increased marginally (4.4%) from 7.67at 6 to 8.01 mg kg-1 DM at 14 weeks. The changes inCa levels with age of the legume were inconsistent.This inconsistency was also reflected in thedetermined Ca:P ratios. This study has shown that,relative to ruminant mineral requirements, V. villosahas adequate macro-elements. The levels of traceelements however, fell below the desired limits forruminants. It was concluded that, advancing age of V.villosa did not have significant effect on tissueconcentration of most essential minerals.